2002
DOI: 10.1634/stemcells.20-6-542
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Senile Osteoporosis in SAMP6 Mice by Intrabone Marrow Injection of Allogeneic Bone Marrow Cells

Abstract: The SAMP6 mouse (a substrain of senescenceaccelerated mice) spontaneously develops osteoporosis early in life and is, therefore, a useful model for examining the mechanisms underlying osteoporosis. We have recently established a new bone marrow transplantation (BMT) method: the bone marrow cells (BMCs) of normal allogeneic mice are directly injected into the bone marrow (BM) cavity of irradiated (5.5 Gy × 2) recipients (IBM-BMT). Using IBM-BMT, we attempted to prevent osteoporosis in SAMP6 mice. The hematolymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 32 publications
2
81
0
Order By: Relevance
“…25 Finally, transplantation of bone marrow cells in a murine model of a severe genetically linked osteoporosis was followed by rapid amelioration of the pathologic phenotype with a slow reversion to the pretreatment status over time. 26,27 How, then, does one explain high levels of osteopoietic engraftment early after BMT with diminishing osteopoietic chimerism over time? Bone is a dynamic tissue undergoing continuous remodeling with high cell and matrix turnover.…”
Section: Discussionmentioning
confidence: 99%
“…25 Finally, transplantation of bone marrow cells in a murine model of a severe genetically linked osteoporosis was followed by rapid amelioration of the pathologic phenotype with a slow reversion to the pretreatment status over time. 26,27 How, then, does one explain high levels of osteopoietic engraftment early after BMT with diminishing osteopoietic chimerism over time? Bone is a dynamic tissue undergoing continuous remodeling with high cell and matrix turnover.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we and others have documented the remarkable advantages of intrabone-marrow (IBM)-BMT over intravenous (IV)-BMT in refractory BMT settings, such as [normal3 MRL/lpr mice] [8] and [human BMCs3 SCID mice] [3,4,9]. Moreover, we have found recently that senile osteoporosis in SAMP6 mice can be prevented and treated effectively by IBM-BMT using BMC from healthy mice [10,11]. In the recipient mice, the proliferation of donor stromal cells was also observed at the site of injection [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have found that IBM-BMT can be used to prevent and treat osteoporosis in SAMP6 mice. 15 We therefore believe that this method (IBM-BMT in conjunction with the Perfusion Method) will become a powerful new strategy for the treatment of various intractable diseases. Furthermore, we believe that this method will become a valuable strategy in regeneration therapy for injured organs and tissues (osteoporosis, emphysema, myocardial infarction, cerebral infarction, Alzheimer's disease, etc), since IBM-BMT can efficiently reconstitute the recipient with both donor-derived hemopoietic stem cells and MSCs.…”
Section: Discussionmentioning
confidence: 99%